Modeling decisions for artificial intelligence : 15th International Conference, MDAI 2018, Mallorca, Spain, October 15-18, 2018, proceedings /: 15th International Conference, MDAI 2018, Mallorca, Spain, October 15-18, 2018, proceedings. (2018) - Unknown
No abstract available